Hierarchical zeolites obtained by alkaline treatment for enhanced n-pentane catalytic cracking. (1st April 2022) - Wang, Zijian; Zhang, Rongxin; Wang, Jieguang; Yu, Zhongwei; Xiang, Yanjuan; Kong, Lingjiang; Liu, Hongquan; Ma, Aizeng
Highlights: A controllable desilication method to form hierarchical nano-sized ZSM-5 zeolites. Hierarchy factor and hydrogen transfer coefficient relate to desilication degree. Mesoporosity contributes to enhanced catalytic and anti-coke performance. Abstract: This study manufactured various hierarchical ZSM-5 zeolites using NaOH, NaAlO2, Na2 CO3, K2 CO3 and NaHCO3 solutions through post-treatment. Later, X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), X-ray fluorescence (XRF), N2 adsorption and desorption, solid state 29 Si and 27 Al MAS NMR, ammonia temperature programmed desorption (NH3 -TPD) as well as pyridine adsorption infrared spectra (Py-FTIR) were carried out to characterize their structure properties and acidities. Further, this study investigated n -pentane catalytic cracking for producing the light olefins over hierarchical nano-sized ZSM-5 zeolites. Alkaline treatment with milder NaHCO3 was much more controllable and reasonable than treatment with other alkalis, which not only adjusted the acidity to promote n -pentane activation, but also formed hierarchical structures combing micropores and mesopores to reduce diffusion resistance and suppress secondary reaction contributing to an enhanced catalytic ability and anti-coke deposition performance. Among the catalysts, ZNaHCO3 exhibited ∼92% the highest n -pentane conversion and ∼50% light olefins selectivity during n -pentane catalytic cracking under 590 °C for 300 min, simultaneously, and these figures markedly increased relative to those for the parent ZSM-5 zeolite. Most importantly, it was also proved that HTC values are relevant to the degree of effectiveness of NaHCO3 desilication, and that mesopore formation contributes to the desirable selectivity of light olefins and coke amount.